ナンキョク ニ オケル ジンコウ ジシン カンソク ノ ガイヨウ ゾク - 伊藤, 潔; イトウ, キヨシ; 伊神, 煇; イカミ, アキラ; 渋谷, 和雄; シブヤ, カズオ; 神沼, 克伊; カミヌマ, カツタダ; 片岡, 信一; カタオカ, シンイチ; Ito, Kiyoshi; Ikami, Akira; et al. (1983)
P(論文) 南極大陸の地殻構造研究のため, 第21次日本南極地域観測隊では人工地震探査を実施した。これらの概要と簡単な結果について述べる。1980年5,6月にオングル諸島周辺および東オングル島内において, 小規模な実験を実施し, 露岩域の地震波速度を求めた。P波の速度は6.0-6.3km/sである。7月には宗谷海岸において大陸での予備実験を実施し, 雪氷ボーリング, 爆破, 観測などのテストを実施して, -30℃以下の低温下で実験が可能なことを確かめた。同時に雪氷下の岩盤の速度が得られ, 6.0-6.2km/sであった。10月から11月にかけて, みずほ-昭和基地間約300kmの測線での大爆破実験を実施した。この測線上27点に計器を設置し, みずほ基地付近および測線の中点において, それぞれ1.4および1.0tの爆破を実施した。これらの爆破孔は, それぞれ140および100mの深さである。さらに1981年1月には, 同じ測線上で, リュツォ・ホルム湾内における3tの爆破を観測した。これらによって得られたみかけ速度は6.0-6.4km/sであり, 深くなるほど速くなる傾向を示した。また, P_n(モホ面による屈折波)は7.9km/sである。下部地殻は初動としてはあらわれないが, 6.9km/sのみかけ速度が得られた。 Seismic refraction experiments were carried out to investigate the crustal structure in Antarctica by the wintering party of the 21st Japanese Antarctic Research Expedition. Five experiments were made from May 1980 to January 1981 in the vicinity of Syowa Station and in Mizuho Plateau, East Antarctica. The outline of the experiments is reported with respect to the field operation and the preliminary results. In May and June 1980,the shallow structure of an ice-free area in the vicinity of Syowa Station, Ongul Islands, was revealed by small-scale experiments. The P-wave velocity in this area is 6.0-6.3km/s. In July a preliminary experiment was conducted in the ice field on the Soya Coast along a line of about 10km long, in which many tests were performed for ice drilling, blasting of dynamite and installation of recording system at air temperature as low as -30℃. Shallow structure of this area was also obtained in the experiment. The P-wave velocity under the ice sheet is 6.0-6.2km/s which is nearly the same as that of the ice-free area. After the success of the experiments two large experiments were conducted along a line of about 300km long between Syowa and Mizuho Stations from October 1980 to January 1981. Explosions of 1400 and 1000kg in charge amount were fired in an ice hole of 143m deep at one end of the line near Mizuho Station and 100m deep at the middle of the line, respectively. In addition to the shots a large explosion of 3000kg in charge ...